Titers of lentiviral vectors encoding shRNAs and miRNAs are reduced by different mechanisms that require distinct repair strategies - Liu, Ying Poi (Cold Spring Harbor Laboratory Press, 2010)
RNAi-based gene therapy is a powerful approach to treat viral infections because of its high efficiency and sequence specificity. The HIV-1-based lentiviral vector system is suitable for the delivery of RNAi inducers to HIV-1 susceptible cells due to its ability to transduce nondividing cells, including hematopoietic stem cells, and its ability for stable transgene delivery into the host cell genome. However, the presence of anti-HIV short hairpin RNA (shRNA) and microRNA (miRNA) cassettes can negatively affect the lentiviral vector titers. We show that shRNAs, which target the vector genomic RNA, strongly reduced lentiviral vector titers but inhibition of the RNAi pathway via saturation could rescue vector production. The presence of miRNAs in the vector RNA genome (sense orientation) results in a minor titer reduction due to Drosha processing. A major cause for titer reduction of miRNA vectors is due to incompatibility of the cytomegalovirus promoter with the lentiviral vector system. Replacement of this promoter with an inducible promoter resulted in an almost complete restoration of the vector titer. We also showed that antisense poly(A) signal sequences can have a dramatic effect on the vector titer. These results show that not all sequences are compatible with the lentiviral vector system and that care should be taken in the design of lentiviral vectors encoding RNAi inducers.